Measuring socio-economic development of rural households: scale development - Niyaz Panakaje; S. M. Riha Parvin; Arun A. Bhagwath; Abbokar Siddiq; Shakira Irfana; Yatheen A (Cogent Social Sciences)
Calibrating socio‑economic development is indispensable for evaluating a country’s progress and identifying areas for improvement. This study aims to establish a measuring scale for evaluating the various socio‑economic development indicators of rural households. The methodology involved critical examination of existing literature and in‑depth interviews with subject experts and respondents to identify different constructs and measurement scales. The indicators of socio‑economic development included social, economic, political, physical assets, health, employment, education, and financial aspects. The indicators’ content, convergent, discriminant, construct validity, EFA, and CFA were examined. Some constructs required additional items, which were obtained through in‑depth interviews. Despite the range of indicators and measurement tools available such as HDI, MPI, and others, still there is a need for a comprehensive set and overall picture of the SED scale. The developed measurement scale is felicitous to assess the socio‑economic development of rural communities in longitudinal studies and to quantify the impact of various independent factors such as rural development programs, financial literacy, financial inclusion, community services, and CSR activities on the SED of rural population. This scale may help government surveys evaluate the state of rural areas now and execute the necessary policy changes for long‑term prosperity and regional growth.